2015
DOI: 10.1002/cne.23938
|View full text |Cite
|
Sign up to set email alerts
|

Expression dynamics of NADPH oxidases during early zebrafish development

Abstract: Nicotinamide dinucleotide phosphate oxidases (NOX) control various cellular signaling cascades. In the nervous system, there is recent evidence that NOX-derived reactive oxygen species (ROS) regulate neurite outgrowth, regeneration, and stem cell proliferation; however, a comprehensive NOX gene expression analysis is missing for all major model systems. Zebrafish embryos provide an excellent model system to study neurodevelopment and regeneration because they develop quickly and are well suited for in vivo ima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(22 citation statements)
references
References 60 publications
(98 reference statements)
1
21
0
Order By: Relevance
“…We used zebra sh as the animal model to explore the function of NOX5. The result of spatiotemporal expression spectrum of NOX5 in zebra sh embryo indicated that NOX5 might play a role in the early development of zebra sh, which is similar to the previous study about the expression of NOX family in zebra sh (28). However, after completely knockdown the NOX5 protein, our results showed that there no difference in HuC/D positive neurons number of GI between the normal group and the NOX5 knockdown group, indicated that the development of ENS in zebra sh did not require the NOX5.…”
Section: Discussionsupporting
confidence: 88%
“…We used zebra sh as the animal model to explore the function of NOX5. The result of spatiotemporal expression spectrum of NOX5 in zebra sh embryo indicated that NOX5 might play a role in the early development of zebra sh, which is similar to the previous study about the expression of NOX family in zebra sh (28). However, after completely knockdown the NOX5 protein, our results showed that there no difference in HuC/D positive neurons number of GI between the normal group and the NOX5 knockdown group, indicated that the development of ENS in zebra sh did not require the NOX5.…”
Section: Discussionsupporting
confidence: 88%
“…However, most of those studies were performed in monocyte/macrophage leukaemia cell lines (Marzaioli et al., ), and the physiological role of neutrophil NOX5 is unclear. In the developing zebrafish, Nox5 is expressed throughout the CNS and, together with Nox2, it might be important in neurodevelopment and regeneration (Weaver et al., ; Weaver, Leung, & Suter, ). This is confirmed in human oligodendrocytes, which require NOX5 for differentiation and maturation (Accetta et al., ).…”
Section: Expression Of Nox5 In Physiological and Pathological Conditionsmentioning
confidence: 99%
“…Nox proteins with the exception of Nox4, which is constitutively active, are silent in resting cells [Lassegue et al, 2012]. characterized in mammalian neurons, NOX proteins including NOX1, NOX5 and DUOX have a dynamic expression pattern during early development of the nervous system of zebrafish (as assayed in zebrafish [0-2 days post fertilization]), while cybb2/NOX2 is stably expressed during this period of development [Weaver et al, 2016]. More indepth examination has revealed that components of the NOX complex such as p40 phox colocalize with F-actin in growth cones [as assayed using the mollusc Aplysia; [Munnamalai et al, 2014] (Fig.…”
Section: Nadph Oxidases: F-actin Effects and Cellular Functions (Withmentioning
confidence: 99%